IRE (Islamic Religious Education) Learning as an Effort to Mitigate Radicalism in Private Islamic Primary Education - Sufirmansyah, Sufirmansyah; Dodi, Limas (Journal of Islamic Studies and Civilization, 2025)
This article aims to explore efforts to prevent radicalism through IRE learning at SD Plus Rahmat Kediri. This article is based on qualitative field research with a phenomenological approach. Data were collected through in-depth interviews, non-participant observation, and documentation. The collected data were then analyzed using Cresswel's spiral model, which includes the following stages: preparing the data; reading through the data; coding the data; describing the setting, categories, and themes to be analyzed; presenting the descriptions and themes in the form of a narrative; and interpreting the data. The author triangulated techniques and sources to maintain data validity. This article concludes that SD Plus Rahmat Kediri has designed and developed a program to prevent radicalism. Efforts made by the school are selecting textbooks, developing teaching modules by teachers, and implementing activities related to nationalism. The strategy is implemented through IRE learning, both in the classroom and outside the classroom. In-class learning includes objectives, materials, media, methods, and evaluation. Learning outside the classroom includes activities related to extracurricular activities, religion, and nationalism.